THE USE OF THE TRANSPORT INFRASTRUCTURE CAPACITY ON THE BRNO-MALOMĚŘICE – TIŠNOV LINE SECTION BEFORE AND AFTER THE INTRODUCTION OF DIVERSION ROUTES FROM THE CZECH FIRST TRANSIT CORRIDOR (Perner's Contacts, 2022)
This article evaluates the use of the transport infrastructure capacity on the Brno-Maloměřice – Tišnov line section using the methodology of Správa železnic (Czech railway infrastructure manager) according to SM 124. First, the planned and actual traffic is determined in terms of its intensity and the type of composition of trains before and after the introduction of diversion routes from the Czech first transit corridor. Subsequently, the capacity of both tracks in all interstation sections is evaluated. Furthermore, the issue of the insufficient number of platforms in the station Tišnov is discussed and a solution according to the authors and according to the planned reconstruction project is presented. There are also presented the results of a separate traffic simulation at the junctions in the St. 3 of the station Brno-Maloměřice and at the set of junctions in the station Tišnov from the side of the station Kuřim.
Keywords: capacity of railway infrastructure; railway; IDS JMK (Integrated Transport System of South-Moravian Region); railway transport dispatching; separate simulation